Yoga as a universal science - "Krishnananda, Swami" (Tehri-Garhwal, 1997)
This book is a compilation of lectures given by the most respected disciple of Swami Sivananda and a learned scholar. The theme is to enlighten the seeker about the real meaning of YOGA and it's universality cutting across all the religions. A must for a genuine student of YOGA.
Keywords: Yoga